Metallic nano carrier complex targeting neuroendocrine prostate cancer - Hemben, Aver; Chianella, Iva; Leighton, Glenn J. T. (Cranfield University, 2019)
Poster presented at Cranfield University’s 2019 Manufacturing Doctoral Community event.
Keywords: NEPC; drug delivery; MDC19 poster; Cancer; Medicine